Pengaruh Harga, Fasilitas, Lokasi, Lingkungan dan Pendapatan Terhadap Keputusan Pembelian Rumah di Kota Bekasi - Putri Fauziyah; Uswatun Khasanah; Agus Salim (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2023)
The need for shelter is one of the fundamental human needs, following clothing and food. Bekasi City is currently experiencing growth and has become a residential area for urban residents and an industrial center. This urbanization is driving population growth, leading to an increased demand for housing. This research aims to examine the influence of price, facilities, location, environment, and income on the decision to purchase a house in the Taman Mula Sakti Indah Housing Complex. The research is a survey study conducted using questionnaires to collect data. The population in this study consists of consumers in the Taman Mula Sakti Indah Housing Complex. The research sample was determined using the Slovin formula, resulting in a sample size of 88 respondents. The data analysis technique used in this study is multiple linear regression analysis. The research findings indicate that collectively, the independent variables, namely price, facilities, location, environment, and income, have a significant simultaneous influence on the dependent variable, which is the purchase decision. Partially, price, location, and income significantly influence the purchase decision variable (Y) in the Taman Mula Sakti Indah Housing Complex.